Physiological Analysis of Eucalyptus pellita F. Muell Shoot Cuttings in Propagation Without the Application of Hormones - Fadhlurrahman, Muhammad Miftah; Budi, Sri Wilarso; Wulandari, Arum Sekar (Journal of Tropical Silviculture, 2024)
The plant species commonly used in Industrial Plantation Forests as raw material for pulp and paper is Eucalyptus pellita. One of the quality seeds of E. pellita is produced from superior clones by vegetative propagation, namely shoot cuttings. There are research results that show the propagation of certain clones has the highest Survival Rate when treated without using additional hormones. Therefore, it is necessary to conduct research on the propagation of E. pellita seed cuttings without using hormones. The results of the physiological analysis of E. pellita shoot cuttings showed that each parameter observed, namely IAA hormone content, C-organic, and N value, showed non-linear results with shoot age treatment. The results of measuring shoot length, number of nodes, and distance between nodes showed linear values with shoot age treatment. The results of observations of total Survival Rate, total roots and shoots showed that the 18 day shoot age treatment had the lowest value compared to other treatments. At the age of 2 weeks, it showed that the 21 day shoot age treatment had the fastest root growth ability compared to other treatments. Based on the results of height and diameter measurements at 12 weeks, it shows that 21 day old shoots have the best growth and Survival Rate so that they can be used as a basis for determining the age of shoots in the production of clone 148 seedlings on an operational scale. Keywords: E. pellita, physiological, propagation, hormone